GAMBARAN KONSEP DIRI PADA REMAJA YANG MENGALAMI JERAWAT DI SMA NEGERI 8 PONTIANAK - Alfiya, Siti; Maulana, M. Ali; Rahmawati, Nadia; Fahdi, Faisal Kholid; Mita, Mita (School of Nursing, Faculty of Medicine, Tanjungpura University, 2025)
Background: The problem with physical changes commonly experienced by teenagers is acne. Teenagers who experience acne often feel embarrassed and close themselves off from their environment, which affects their self-concept. Objective: To determine the description of self-concept in adolescents who experience acne at Senior High School 8 Pontianak. Method: The research method uses quantitative research with purposive sampling techniques. By carrying out total sampling in accordance with the inclusion criteria, a sample size of 110 respondents from classes X and XI was obtained. Results: The results were that teenage girls experienced the most acne at 71.8% and experienced low self-concept. 74.5% of teenagers are experiencing acne. Conclusion: It can be concluded that the teenagers who experience the most acne in adolescence are female teenagers with low self-concept.